Gynaecological malignancies after breast cancer diagnosis: A population-based study - Barretina-Ginesta, Maria Pilar; Galceran, Jaume; Pla, Helena; Meléndez, Cristina; Bague, Anna Carbo; Ameijide, Alberto; Carulla, Marià; Barretina, Jordi; Izquierdo, Angel; Marcos-Gragera, Rafael (Clinical Journal of Obstetrics and Gynecology, 2019)
Background: Breast cancer (BC) is one of the most prevalent malignancies. BC survivors have higher risk of second primary cancers than the general population. There is an increased interest in BC survivor management, including the prevention of these second cancers. The aim of this study was to assess the risk of gynaecological malignancy (GM) as second neoplasm among BC patients in our population. Methods: Patients with invasive BC diagnosed from 1980 to 2014 included in the Girona Cancer Registry were included. The incidence of second GM in these patients was compared to those in the general population. Second primary cancer was stated as a tumour diagnosed after 2 months from the BC diagnosis. Standardized incidence ratios (SIR) and absolute excess of risk (AER) were calculated. Results: 9,717 patients were diagnosed with invasive BC during this period, with a median age at diagnosis of 61 years, and a median follow-up of 7.9 years. 117 of them developed a second GM. By tumour type, the only statistically significant higher SIR was observed for corpus uteri cancer (SIR:2.28 95% CI 1.82-2.83; AER:6.43 95% CI 4.13-9.14). After reviewing the histology of the corpus uteri cancer cases, we found that 71.4% were type I (endometrioid adenocarcinoma), 15.5% type II (serous adenocarcinomas and clear cell carcinomas), 10.7% carcinosarcomas, 2.4% sarcomas and there were no unspecified malignant neoplasms. Conclusion: BC survivors have an increased risk of corpus uteri cancer, with an increase in unfavourable histologies compared to the general population. Lifelong primary and secondary prevention interventions should be recommended for these patients.